Ordinance No. 160, § 1: An Ordinance Defining Offenses Against the Peace and Good Order of the City of Caldwell, and Providing Punishment Therefore, in The Caldwell Tribune, May 27, 1910, at 2 (Caldwell, Idaho) - (:unkn) unknown (My University, 1910)
§ 1: Prohibited discharging an air gun, sparrow gun, flipper, or other similar contrivance within the city limits.
Keywords: DISCHARGE